Environmental impact of the cultivation of energy willow in Poland - Zbigniew Kowalczyk (Nature Portfolio, 2021)
Abstract The purpose of the work is to analyze the structure of the environmental impact of energy willow cultivation (Salix spp.) on plantations of various sizes, divided per materials and processes. The research covered 15 willow plantations, ranging from 0.31 ha to 12 ha, located in southern Poland. It was found, among others, that the so-called processes, i.e. the use of technical means of production, dominate the structure of the environmental impact (EI) related to the cultivation of energy willow, and that the cultivation of energy willow on larger plantations has a much lower environmental impact compared to cultivation on smaller plantations. Also, in the case of the environmental impact of processes, the largest environmental impact was recorded in the human health category, which is mainly associated with the consumption of fuel, i.e. diesel. It was determined, e.g., that the cultivation of energetic willow on larger plantations is characterized by a much lower environmental impact (as per the cultivation area), at approx. 108 Pt, compared to the cultivation on smaller plantations, where the value of the environmental impact is 168 Pt. A decisively dominant position in the structure of the environmental impact (EI), related to the cultivation of energy willow, is held by the so-called processes, i.e. the use of technical means of production. Their share in the total environmental impact decreases from 148.5 Pt in the group of the smallest plantations to 77.9 Pt in the group of the largest plantations.